Knowledge of kinnow growers with respect to the recommended practices including post harvest technology - Singh, Kuldeep; Dangi, K.L.; Singh, Narpat (Annals of Agricultural Research, 2017)
The study was conducted in Sri Ganganagar and Sri Karanpur panchayat samities of Sri Ganganagardistrict. The majority of respondents (63.30 per cent) were from medium knowledge category, while17.30 per cent placed under high category. The proportion of respondents the low knowledge was19.33 per cent. The extent of knowledge of big farmers were found to be substantially higher thanthe small farmers about recommended practices of kinnow cultivation. Results indicated that therewas significant difference in knowledge between small and big farmers regarding recommendedpractices of kinnow cultivation in the study area.